Isolation and Identification of Flavonoid Compound from the Rambutan Stem Bark (Nephelium lappaceum L.) - Helmina Sembiring; Mesy Jelisa (Talenta Publisher, 2024)
Flavonoids derived from the stem barks of Rambutan (Nephelium Lappaceum L.) have been extracted. The extraction of Rambutan stem bark was performed by maceration using a methanol solvent. The concentrated methanol extract was diluted in ethyl acetate until the solution became devoid of all positive and flavonoid compounds. The highly concentrated ethyl acetate extract was subsequently dissolved using methanol and separated into different parts using an n-hexane. The methanol content was determined using thin-layer chromatography and separated using column chromatography using eluent chloroform: methanol in various ratios (90:10, 80:20, 70:30) v/v. The chemicals were purified using preparative thin-layer chromatography (TLC) and yielded 7.9 mg of amorphous solids with an Rf value of 0.25. The eluent was a chloroform and ethyl acetate mixture in a 50:50 volume-to-volume ratio. The substance was analyzed using Spectrophotometer Ultraviolet Visible (UV-Vis), Fourier Transform Infra Red Spectrophotometer (FT-IR), and Proton Nuclear Magnetic Resonancy Spectrophotometer (1H-NMR). The analysis identified the chemical as a flavonoid of the flavonol.